Developing local-based invertebrates e-encyclopedia to improve scientific reasoning skills - Maisuna Kundariati; Fatchur Rohman (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Acknowledging that it is one of the important of 21st Century skills, scientific reasoning skills have been developed in various ways. However, the development based on local potential has not been optimally explored yet. The aim of this research was to produce e-encyclopedia of invertebrates based on local potency to improve students’ scientific reasoning skills. This research and development was done, based on Lee and Owen development model, between July and December 2019. This research involved 29 students of Biology Department, Universitas Negeri Malang who have passed their third semester. The validity of e-encyclopedia was determined by conducting expert appraisal consisted of the instructional and technical review. The assessments towards e-encyclopedia was done to decide its validity, practicality, and effectiveness. Furthermore, the students’ scientific reasoning skills were measured using pretest and posttest. The validity data obtained were analyzed descriptively using percentage, while students’ scientific reasoning skills were analyzed using gain scores. The results showed that the percentage values were 84.72 for content validity (valid), 98.10 for media (very valid), 87.41 for technical (very valid), and 84.47 for practicality (valid). In addition, the students’ scientific reasoning skills were classified as effective based on the gain scores achieved in each indicator i.e. 0.44 (argumentation), 0.43 (existing knowledge), 0.38 (methodology), 0.40 (analysis), and 0.42 (drawing conclusions). Thus, the e-encyclopedia developed is effective to improve students’ scientific reasoning skills.